Mitochondrial tRNA Mutation and Regulation of the Adiponectin Pathway in Maternally Inherited Hypertension in Chinese Han - Bai, Jing; Ma, Qiang; Lan, Yunfeng; Chen, Yating; Ma, Shanshan; Li, Jiaxin; Liu, Chuanbin; Fu, Zihao; Lu, Xu; Huang, Yun; Li, Yang (Frontiers in Cell and Developmental Biology, 2021)
Some essential hypertension (EH) patients show maternal inheritance, which is the mode of mitochondrial DNA inheritance. This study examined the mechanisms by which mitochondrial mutations cause EH characterized by maternal inheritance. The study enrolled 115 volunteers who were divided into maternally inherited EH (group A, n=17), non-maternally inherited EH (group B, n=65), and normal control (group C, n=33) groups. A mitochondrial tRNA (15910 C>T) gene mutation was significantly correlated with EH and may play important roles in the pathogenesis of maternally inherited EH. Examining two families carrying the mitochondrial tRNA 15910 C>T mutation, which disrupted base pairing and may affect the stability and function of mitochondrial tRNAThr, we found that the overall incidence of EH was 59.3% in the maternal family members and 90% in males, significantly higher than in the general population in China (23.2%), and that the EH began at a younger age in those carrying mitochondrial tRNA 15910 C>T. To reveal the mechanism through which mitochondrial tRNA 15910 C>T caused maternally inherited EH, we cultured human peripheral blood mononuclear cells from family A2 in vitro. We found that cells carrying mitochondrial tRNA 15910 C>T were more viable and proliferative and the increased ATP production resulted in raised intracellular reactive oxygen species (ROS). Moreover, the mitochondrial dysfunction resulted in reduced APN levels, causing hypoadiponectinemia, which promoted cell proliferation, and produced more ROS. This vicious cycle promoted the occurrence of EH with maternally inherited mitochondrial tRNA 15910 C>T. The mitochondrial tRNA 15910 C>T mutation may induce hypertension by changing the APN, AdipoR1, PGC-1α, and ERRα signaling pathways to elevate blood pressure. We discovered a new mitochondrial mutation (tRNA 15910 C>T) related to EH, revealed part of the mechanism by which mitochondrial mutations lead to the occurrence and development of maternally inherited essential hypertension, and discussed the role of APN in it.